Green Accounting and Hospital Sustainability: A Quadruple Bottom Line Analysis at XKP Cirebon Hospital - Fergi Ferdiansyah; Wiwit Apit Sulistyowati (Politeknik Ganesha Medan, 2026)
Background: Hospitals produce medical and non-medical waste, contributing 28.6-36% of global healthcare carbon emissions paradoxical for health-protecting institutions. Yet green accounting practices for measuring and disclosing environmental costs remain underdeveloped in Indonesian hospitals. Objective: This study explores green accounting implementation at a private hospital in Cirebon, analyzes its contribution to sustainability via the Quadruple Bottom Line framework, and formulates optimization strategies. Method: A qualitative interpretive case study design was employed. Data were collected through in-depth interviews with five key informants, non-participatory observation of the waste management system, and analysis of financial reports, hazardous waste recapitulation data, and operational environmental documents covering 2023-2024. Thematic analysis was performed using an interactive model with source and method triangulation. Results: Total identified environmental costs increased from IDR 341.66 million in 2023 to IDR 383.14 million in 2024, representing a 12.14% rise and comprising approximately 0.81% of total operating costs below the international sustainability benchmark of 1.5-2.0% for committed hospitals (Dolcini et al., 2025), yet consistent with comparable studies in Indonesian hospital settings. These costs, however, remain undisclosed in formal financial statements. Quadruple Bottom Line analysis confirms positive contributions across all dimensions: a 10% reduction in wastewater treatment costs, zero infectious waste accidents with 85% staff environmental awareness, 95-100% hazardous waste compliance, and strong institutional ethical governance rooted in a holistic service philosophy. Conclusion: Green accounting supports hospital sustainability but remains unsystematized. This study proposes a Quadruple Bottom Line-based model to guide Indonesian private hospitals toward integrated green accounting.